Morphological and molecular identification of endophytic fungi from roots of epiphyte orchid Aerides odorata Lour in Sabah - Nor Amirah Shamsudin; Jaya Seelan Sathiya Seelan; Jualang Azlan Gansau; Nor Azizun Rusdi (Springer Nature, 2025)
Aerides odorata Lour is an epiphyte, a valuable orchid for its beauty, fragrance and medicinal uses. Identifying beneficial orchid mycorrhizal fungi is important for improving the success of tissue culture and transplantation into the original habitats. This study aimed to identify and characterise endophytic mycorrhizal fungi associated with the roots of the endangered epiphyte A. odorata. The study examined fungal isolates cultured on potato dextrose agar (PDA), analysing macro- and micromorphological characteristics using Field Emission Scanning Electron Microscopy (FESEM). Molecular identification using nuclear ribosomal DNA (nrDNA) and the internal transcribed spacer (ITS) region analysis confirmed the isolates’ species identity. The fungi were found to be tightly packed and dense in cortical cells, forming pelotons and indicating active colonisation. Seven fungal genera were isolated and successfully identified, including Fusarium spp., Clonostachys sp., Biscogniauxia sp., Daldania sp., Trichoderma sp., and Murinectria sp. Most isolates exhibited a cottony or simple radial texture, although some isolates, like FNRAO13 and UNNRAO9, display a velvety or shaped pattern. The mature colony colours varied among the isolates, and their growth rate ranges from 2.4 mm/day to 8.83 mm/ day, reflecting significant variability in growth pattern among isolates. The result provides valuable baseline data for future studies in identifying a variety of mycorrhizal fungi and their functional roles in orchid conservation strategies.